2020
DOI: 10.1016/j.gca.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the importance of authigenic clay formation in the global Li cycle

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 67 publications
1
22
0
Order By: Relevance
“…Andrews et al. (2020) find that a proportion of this flux (80 × 10 9 g/year) is found in authigenic clays associated with carbonate‐rich sediments. Independent evidence supports preferential incorporation of 6 Li by clay minerals, which presumably begins with the formation of secondary clay minerals in soils and continues in rivers and marine sediments (Lemarchand et al., 2010; Ma et al., 2020; Steinhoefel et al., 2021; J.‐W.…”
Section: Natural Biogeochemical Cyclementioning
confidence: 99%
“…Andrews et al. (2020) find that a proportion of this flux (80 × 10 9 g/year) is found in authigenic clays associated with carbonate‐rich sediments. Independent evidence supports preferential incorporation of 6 Li by clay minerals, which presumably begins with the formation of secondary clay minerals in soils and continues in rivers and marine sediments (Lemarchand et al., 2010; Ma et al., 2020; Steinhoefel et al., 2021; J.‐W.…”
Section: Natural Biogeochemical Cyclementioning
confidence: 99%
“…Li and Sr are widely used to estimate several geochemical processes notably at the water/ rock interface (Huh et al, 1998;Brunskill et al, 2003;Davis et al, 2003) such as continental weathering (Pistiner and Henderson, 2003;Vance et al, 2009;Millot et al, 2010) or hydrothermal alteration of oceanic crust (Barker et al, 2008;Araoka et al, 2016;Chavagnac et al, 2018a). It is generally admitted that dissolved riverine inputs and hydrothermal inputs are the two main sources of Li and Sr to the ocean (Albarède et al, 1981;Palmer and Edmond, 1989;Allègre et al, 2010;Tomascak et al, 2016;von Strandmann et al, 2020). Nevertheless, there are still unresolved issues concerning the complex Li and Sr oceanic budget (Stoffynegli and Mackenzie, 1984;Huh et al, 1998;Davis et al, 2003;Vance et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are still unresolved issues concerning the complex Li and Sr oceanic budget (Stoffynegli and Mackenzie, 1984;Huh et al, 1998;Davis et al, 2003;Vance et al, 2009). The isotopic composition of marine Li is heavier than that of its sources, implying that there are sinks that preferentially remove light Li, i.e., secondary clay formation (Tomascak et al, 2016;von Strandmann et al, 2020). However, uncertainties remain regarding, for example, the impact on the marine Li isotope budget of groundwater discharges (Mayfield et al, 2021), or of clay authigenesis (Andrews et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that partial dissolution of basalt does not result in Li-isotope fractionation, but that granite dissolution can cause such fractionation (Pistiner and Henderson 2003;Négrel and Millot, 2019). In addition, adsorption onto mineral surfaces can be another major mechanism of Li-isotopic fractionation in the hydrosphere (Wenshuai and Liu, 2020;Andrews et al, 2020). Moreover, Li is not a nutrient and does not participate in biologically mediated reactions, so no evidence of biological Li-isotope fractionation has been observed to date (Rudnick et al, 2004;Marriott et al, 2004).…”
Section: -Introductionmentioning
confidence: 99%